2022
DOI: 10.3390/pediatric14010006
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Three-Dimensional Printing for Preoperative Assessment of Children with Extra-Cranial Solid Tumors: A Systematic Review

Abstract: Background: In cases with solid tumors, preoperative radiological investigations provide valuable information on the anatomy of the tumor and the adjoining structures, thus helping in operative planning. However, due to a two-dimensional view in these investigations, a detailed spatial relationship is difficult to decipher. In contrast, three-dimensional (3D) printing technology provides a precise topographic view to perform safe surgical resections of these tumors. This systematic review aimed to summarize an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…7,8 While magnetic resonance imaging (MRI) and computed tomography (CT) have been the foundation of preoperative oncologic imaging, 4 incorporating 3D modeling and printing for enhanced visualization appears beneficial. 9 Specifically, within pediatric oncology, previous work has suggested that 3D printing may be useful for complex tumor resections, 10,11 though these techniques have yet to be published within the United…”
Section: Introductionmentioning
confidence: 99%
“…7,8 While magnetic resonance imaging (MRI) and computed tomography (CT) have been the foundation of preoperative oncologic imaging, 4 incorporating 3D modeling and printing for enhanced visualization appears beneficial. 9 Specifically, within pediatric oncology, previous work has suggested that 3D printing may be useful for complex tumor resections, 10,11 though these techniques have yet to be published within the United…”
Section: Introductionmentioning
confidence: 99%
“…Compared with imaging examination results, such as MRI data, 3D printing enables surgeons to more intuitively understand the relationship between tumors and surrounding tissues and to perform preoperative simulation operations. 4,5 Sánchez et al used real-time 3D printing before and during surgery to perform a more thorough and safer resection of complex tumors. About 15% of complicated hepatoblastoma cases cannot be surgically removed after chemotherapy and need liver transplantation.…”
Section: D Printing Technologymentioning
confidence: 99%
“…Three‐dimensional (3D) printing software uses preoperative imaging examination data for 3D visualization and then prints tumors and adjacent tissues and organs using different materials. Compared with imaging examination results, such as MRI data, 3D printing enables surgeons to more intuitively understand the relationship between tumors and surrounding tissues and to perform preoperative simulation operations 4,5 . Sánchez et al.…”
Section: Surgery Planning and Surgical Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many cases of 3D modeling technology in the medical field at home and abroad, mainly used in orthopedic material preparation, thoracic surgery, maxillofacial plastic surgery, hepatobiliary surgery, and other disciplines (2,6,(8)(9)(10)(11). However, there are few reports on the application of this technology in the surgical treatment of complex soft tissue malignant tumors (12). This paper reports the complete resection of a complex soft tissue malignant tumor of the left thigh under the guidance of 3D modeling technology.…”
Section: Introductionmentioning
confidence: 99%